Biogenic Amines - Proestos, Charalampos (IntechOpen, 2019)
Biogenic amines (BAs) are low-molecular-mass organic bases that occur in plant- and animal-derived products. BAs in food can occur by free amino acid enzymatic decarboxylation and other metabolic processes. Usually, in the human body, amines contained in foods are quickly detoxified by enzymes such as amine oxidases or by conjugation; however, in allergic individuals or if monoamine oxidase inhibitors are applied, the detoxification process is disturbed and BAs accumulate in the body. Knowing the concentration of BAs is essential because they can affect human health and also because they can be used as freshness indicators to estimate the degree of food spoilage.